EDUCATING THE NATION I: SCHOOLS*. (24th October 2014) - Mandler, Peter
ABSTRACT: This paper assays the public discourse on secondary education across the twentieth century – what did voters think they wanted from education and how did politicians seek to cater to those desires? The assumption both in historiography and in popular memory is that educational thinking in the post-war decades was dominated by the ideal of 'meritocracy' – that is, selection for secondary and higher education on the basis of academic 'merit'. This paper argues instead that support for 'meritocracy' in this period was fragile. After 1945, secondary education came to be seen as a universal benefit, a function of the welfare state analogous to health. Most parents of all classes wanted the 'best schools' for their children, and the best schools were widely thought to be the grammar schools; thus support for grammar schools did not imply support for meritocracy, but rather for high-quality universal secondary education. This explains wide popular support for comprehensivisation, so long as it was portrayed as providing 'grammar schools for all'. Since the 1970s, public discourse on education has focused on curricular control, 'standards' and accountability, but still within a context of high-quality universal secondary education, and not the 'death of the comprehensive'.